Joint planning and problem solving roles in supply chain collaboration. Issue 1 (March 2017) - Kumar, Gopal; Banerjee, R.N.; Meena, P.L.; Ganguly, Kunal K.
Abstract: This research attempts to uncover joint planning and problem solving roles in developing culture in supply chain collaboration (SCC). This research views collaborative activities as internal and external focussed functional areas. The model is validated with industry data using PLS approach. Findings show that joint problem solving and measurement are critical in developing collaborative culture and executing effective planning; hence it affects core and non-core activities of collaboration. Joint planning at operation level is very important in culture development. This research contributes in developing collaborative culture and making SCC effective. Finally managerial insights and future scope are highlighted.